Figure 3 in Diet of the European eel Anguilla anguilla (Linnaeus, 1758) in two transitional waters of Southwestern Mediterranean - Derbal, Farid; Hamdi, Sandra; Rouag-Laouira, Lydia; Chaoui, Lamya; Kara, Mohamed Hichem (Zenodo, 2022)
Figure 3. – Comparison of the IRI of major items ingested by Anguilla anguilla from Mellah lagoon (in black) and Wadi El Kebir (in gray). Published as part of Derbal, Farid, Hamdi, Sandra, Rouag-Laouira, Lydia, Chaoui, Lamya & Kara, Mohamed Hichem, 2022, Diet of the European eel Anguilla anguilla (Linnaeus, 1758) in two transitional waters of Southwestern Mediterranean, pp. 3-11 in Cybium 46 (1) on page 6, DOI:10.26028/cybium/2022-461-001, http://zenodo.org/record/10836082